Novel Natural Surfactant-Based Fatty Acids and Their Corrosion-Inhibitive Characteristics for Carbon Steel-Induced Sweet Corrosion: Detailed Practical and Computational Explorations - Abd El-Lateef, Hany M.; El-Beltagi, Hossam S.; Mohamed Mohamed, Maged Elsayed; Kandeel, Mahmoud; Bakir, Esam; Toghan, Arafat; Shalabi, Kamal; Tantawy, Ahmed H.; Khalaf, Mai M. (Frontiers in Materials, 2022)
Steel alloys are a significant industrial substantial, but it generally suffers from severe corrosion in harsh conditions. Using inhibitors is an efficacious method to impede corrosion. So, in this work, two novel natural surfactants based on Soybean oil have been synthesized by a facile route, namely: 1-(bis(2-hydroxyethyl)amino)-1-oxooctadecan-9-yl sulfate 2-hydoxyethan-1-aminium (CSM) and –N-(C2H4-OH)2; 1-(bis(2-hydroxyethyl)amino)-1-oxooctadecan-9-yl sulfate bis(2-hyroxyethyl)aminium (CSD) and their chemical structures were elucidated by physical-chemical approaches, Fourier Transform Infrared Spectroscopy (FT-IR) spectroscopy, and surface activity measurements. The inhibitive capability of natural surfactants (CSM and CSD) on the C-steel corrosion in CO2-saturated 3.5% NaCl has been estimated in this investigation by electrochemical and surface analyses beneﬁts including electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), linear polarization resistance (LPR) corrosion rate, X-ray photoelectron spectroscopy (XPS), and field emission scanning electron microscope/ energy-dispersive X-ray spectroscopy (FESEM/EDX) approaches. EIS study reveals the value of Rp augmented to a supreme of 913.5 Ω cm2 with the protection capacity of 96.1% at 150 ppm (CSD). The outcomes of PDP suggested that CSM and CSD are mixed-type inhibitors. XPS and FESEM/ EDX analysis designated the protective film formation on a metal interface having undamaged surface morphology and more homogeneousness in the occurrence of surfactant. Moreover, the adsorption of natural surfactants on the metal substrate takes place based on the model of Langmuir isotherm. Density functional theory (DFT) calculations and Monte Carlo (MC) simulations were selected for attaining basic atomic/electronic-scale details about the prepared surfactants, which support the practical findings. This study is intended to investigate the protection of C-steel used sweet service conditions with green extracts surfactants.